Manipulierter Körper - Verplante Seele? Psychoanalytische und philosophische Überlegungen zum Menschenbild der Medizin unter besonderer Berücksichtigung der deutschsprachigen Literatur - Frick, Eckhard (European Journal of Mental Health, 2009)
Manipulated Body – Planned Soul? Psychoanalytical and Philosophical Considerations Regarding the Image of Man in Medicine, with a Special Focus on German Language Literature: Psychosomatic anthropology carries within it the burden of the duality of two ontologies excluding one another (body–soul or mind–spirit duality). According to those arguing for a holistic approach to therapy, spiritual healing that ignores the body is to be avoided in the same way as corporeal medicine bypassing the soul. As opposed to such holistic statements, this work argues for replacing the traditional metaphysical aporia of medicine with the duality of two points of view, namely the living body (Leib) experienced from the first and second person perspective on the one hand and the physical body (Körper) described from the third person perspective on the other hand. This anthropological theory is based on philosophical anthropology (Plessner), a phenomenological view of the body (Fuchs) and the sociology of the body (Villa). The traditional hysteria model, seized at the dawn of psychoanalysis in a novel way, serves as an example in medical history of the materialization of the living human body.